How does case complexity drive case resolution for RSPO grievance cases? - Phua, Shi Yu (Nanyang Technological University, 2023)
The Roundtable on Sustainable Palm Oil (RSPO) is a non-profit organisation that promotes sustainable palm oil production. It comprises stakeholders from across the palm oil supply chain and requires members to uphold its social and environmental sustainability standards. When a conflict occurs due to potential breaches of the standard, a case may be filed through the RSPO’s grievance mechanism. While causes and outcomes of grievance cases have been explored, the drivers of case resolution remain largely unstudied. Hence, this paper investigates how case complexity drives the way resolution was achieved (i.e., resolution mechanisms) for RSPO grievance cases. We developed a typology of seven case complexity variables (duration, traceability, complicating stakeholders, court involvement, internal grievance mechanisms, mediators, and third-party verification) and related them to four resolution mechanisms (bilateral engagement, case withdrawal, case dismissal, and corrective action), and whether the case was resolved via agreement (i.e., bilateral engagement or corrective action). We find that no single variable fully explains case resolution; rather, different variables seem to be driving forces for different resolution mechanisms. Certain resolution mechanisms are more strongly explained by these variables. Resolution via bilateral engagement was more strongly driven by shorter case duration, a less established internal grievance mechanism, and third-party verification. Meanwhile, case withdrawal was more strongly driven by court involvement, longer case duration, and having fewer than two mediators. In most conflicts, we find that where the courts are involved, the RSPO tends to take a back seat in conflict resolution, instead taking its cue from court rulings.